The Basic Concepts of Faith, Tauhid, and Morals - Fauzy, Husny; Junaedi, Achmad (International Journal of Education, Information Technology, and Others, 2025)
The study of the basic concepts of faith, monotheism, and morality is an important foundation in shaping the personality and spirituality of a Muslim. Faith, as a fundamental belief, serves as the primary foundation for understanding the essence of divinity, which is then elaborated more specifically in the concept of tauhid, namely the belief in the oneness of God in all aspects of life. Tauhid is not merely theoretical but also serves as a practical guideline for performing worship and social interactions. Morality, as a manifestation of true faith and monotheism, reflects moral and ethical qualities in daily life. This study aims to outline the relationship between these basic Islamic concepts and demonstrate how the integration of faith, monotheism, and morality shapes the character of a complete Muslim. This study uses a qualitative descriptive method with a literature review approach. The results indicate that a complete and in-depth understanding of faith and monotheism will give rise to noble morality, which is the primary goal of Islamic teachings